2016
DOI: 10.1038/ismej.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Root microbiota dynamics of perennial Arabis alpina are dependent on soil residence time but independent of flowering time

Abstract: Recent field and laboratory experiments with perennial Boechera stricta and annual Arabidopsis thaliana suggest that the root microbiota influences flowering time. Here we examined in long-term time-course experiments the bacterial root microbiota of the arctic-alpine perennial Arabis alpina in natural and controlled environments by 16S rRNA gene profiling. We identified soil type and residence time of plants in soil as major determinants explaining up to 15% of root microbiota variation, whereas environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
92
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 33 publications
15
92
2
1
Order By: Relevance
“…Recent studies have shown that upon microbiota acquisition, the root-associated bacterial assemblage remains robust against major changes in plant stature and source-sink relationships (9,11). This microbiota stability is also observed here, where a clear separation between the root and rhizosphere of WT and symbiosis-impaired Lotus plants is retained when plants are grown under different nitrate conditions (SI Appendix, Fig.…”
Section: Mutantssupporting
confidence: 56%
See 2 more Smart Citations
“…Recent studies have shown that upon microbiota acquisition, the root-associated bacterial assemblage remains robust against major changes in plant stature and source-sink relationships (9,11). This microbiota stability is also observed here, where a clear separation between the root and rhizosphere of WT and symbiosis-impaired Lotus plants is retained when plants are grown under different nitrate conditions (SI Appendix, Fig.…”
Section: Mutantssupporting
confidence: 56%
“…2B). This similarity is likely related to our stringent root fractionation protocol (10,11), depleting both epiphytes and epidermal endophytes. However, we cannot rule out differences between the communities of the tested mutants of a magnitude smaller than the effect caused by soil batch variation and technical noise present in the pyrosequencing data.…”
Section: Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…soil physiochemical properties) and to a lesser extend selection by the host (e.g. plant genotype) influence the variation of bacterial root microbiota profiles (Bulgarelli et al 2012;Lundberg et al 2012;Peiffer et al 2013;Edwards et al 2015;Dombrowski et al 2017). Selection by the environment and the host are also important drivers of leaf-associated microbiota composition Horton et al 2014;Wagner et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The plant microbiota can influence multiple plant traits such as biomass accumulation (Sugiyama et al 2013), metabolite production , drought tolerance (Lau and Lennon 2012;Rolli et al 2015), flowering time (Wagner et al 2014;PankeBuisse et al 2015;Dombrowski et al 2017) and disease resistance (Busby et al 2016;Ritpitakphong et al 2016;Mendes et al 2011;Santhanam et al 2015).…”
Section: Introductionmentioning
confidence: 99%